_//(2*2) - 4x - 7// * _//2// = 0
4* 12x - 7 * 122/100 = 0
28*12x * ((28*12)/122) = 0
(23/10 * x) * ((23/10 * x)/122) = 0
23/10 *x = 0 / ((23/10 *x)122)
23/10 *x = 0
23/x = 10
x = 2.3
In the context of the equation 2x2=4, "2" represents a numerical value that is being multiplied by itself to yield the result of "4." Therefore, "2" in this context refers to the base number being multiplied by itself.
An imperfect square root, also known as a non-perfect square root, is a square root that is not a whole number. It is an irrational number that cannot be expressed as a simple fraction. For example, the square root of 2 is an imperfect square root because it is approximately equal to 1.41421356 and cannot be simplified further. Imperfect square roots are commonly found when taking the square root of numbers that are not perfect squares.
Yes, because 2x2 equals 4 and 4/2 equal 2
2x2 = 4 , Four . 2x2 = 4 , Four .
What is the solution set of 2x2 + x = 15
In the context of the equation 2x2=4, "2" represents a numerical value that is being multiplied by itself to yield the result of "4." Therefore, "2" in this context refers to the base number being multiplied by itself.
x = square root of 3.
2x2+9 = -412x2 = -41-92x2 = -50x2 = -25x = -5Check: (2*-52)+9 = -41Sorry, you can't have -5 as square root of -25.x = 5i, where i is the imaginary square root of -1
2x2 = 228 divide both sides by 2 x2 = 114 x = ±√114 by the square root property
15,000 to the third power that equals pi plus 12 would make it the square root of 7
The square root of 4 is 2. (2x2 = 4).
Reading this as: 4x2-6=2x2 This implies that: -6=-2x2 3=x2 x=sqrt(3) and x=-sqrt(3) So x can equal plus or minus the square root of 3
2x2 - 3x + 7 = 0 doesn't factor neatly. Applying the quadratic formula, we find two imaginary solutions: (3 plus or minus the square root of -47) divided by 4.x = 0.75 + 1.713913650100261ix = 0.75 - 1.713913650100261iwhere i is the square root of negative 1
2x2-10+7 = 0 Solving the quadratic equation using the quadratic formula will give you two solutions and they are: x = (5 - the square root of 11)/2 or x = (5 + the square root of 11)/2
If 2x2 + 3x + 9 = 0 then x = -0.75 - 1.984i or -0.75 + 1.984i where i is the imaginary square root of -1.
It works out that the centre of the circle is at (-0.5, 1.5) and its diameter is the square root of 28
46Improved answer:First rearrange this quadratic equation which will have two solutions :2x2-10x-6 = 0Simplify the equation by dividing all terms by 2:x2-5x-3 = 0Then by using the quadratic equation formula it will work out as:x = (5 + the square root of 37)/2or x = (5 - the square root of 37)/2